0182 Predictors of Workers' Compensation Claim Duration among Workers Disabled Due to Low Back Pain. (23rd June 2014) - Busse, Jason; Steenstra, Ivan; Ebrahim, Shanil; Heels-Ansdell, Diane; Walter, Stephen; Guyatt, Gordon
Abstract : Objectives: Low back pain (LBP) is a common complaint among workers receiving Workers' Compensation wage replacement benefits. We used the administrative data from the Ontario Workplace Safety and Insurance Board (WSIB) to explore the association between baseline characteristics and commonly reimbursed therapies and time to claim closure among workers disabled due to LBP. Method: Using the WSIB administrative database, we acquired a random sample of 6665 injured workers who reported an uncomplicated back injury (strain or sprain) with a date of injury between January 1, 2005 and June 30, 2005. We selected, a priori, 11 variables from the database that we judged may be associated with claim closure and predicted the direction of anticipated effects. We performed a time-to-event analysis using Cox proportional hazards regression to assess the association between time to claim closure and the independent variables. Receipt of WSIB-reimbursed chiropractic care or physiotherapy were treated as a time-dependent covariate to account for when treatment was initiated during the course of the disability claim. Results: Our adjusted regression analysis showed that older age and opioid prescription (adjusted hazard ratio [HR]=0.69; 99% CI=0.53, 0.89) in the first 4-weeks of claim reimbursed by the WSIB were associated with prolonged claim closure, whereas working for an employer that had a return-to-work program was associated with shorter claim duration (adjusted HR=1.73; 99% CI=1.42, 2.12). Neither reimbursement for chiropractic or physiotherapy were associated time to claim closure. Conclusions: Our analysis suggests that commonly reimbursed treatment for Workers' Compensation LBP claimants may be ineffective or even harmful.